Analisis Yuridis Mengenai Sengketa Tanah Bekas Milik Belanda Antara Masyarakat Dengan Pt Kereta Api Indonesia (Persero) Berdasarkan Putusan Pengadilan Nomor 1145/Pdt.G/2023/Pn.Sby - Wedistya, Febrian Putra; Nugroho, Eko Rial (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This research aims to juridically analyze the judge’s considerations in the Surabaya District Court Decision Number 1145/Pdt.G/2023/PN.Sby and to assess the compatibility of the ruling with land law principles and prevailing legal regulations in Indonesia. The research method employed is normative juridical, using statutory and case approaches. The findings indicate that the community’s occupation of the land is not fully recognized under positive law due to the absence of formal ownership evidence, while PT. Kereta Api Indonesia (Persero) bases its claim on the land’s status as a state asset inherited from the colonial period, which has not been officially transferred. The court's decision affirms the legal standing of PT. Kereta Api Indonesia (Persero) as the rightful party to the disputed land. The land ownership dispute over former Dutch property between the local community and PT. Kereta Api Indonesia (Persero) is a complex legal issue, deeply intertwined with historical, administrative, and civil rights aspects. This study recommends a reformulation of policies regarding the redistribution of former colonial lands to ensure legal certainty and justice for the affected communities